Political Education Methods in the Islamic Perspective: An Analysis of the Political Education Methods Employed by Prophet Muhammad SAW - Amsori Amsori (Sekolah Tinggi Agama Islam Al-Jami Banjarmasin, 2026)
This study examines the methods applied by the Prophet Muhammad SAW in political education based on the Qur'anic perspective. Indonesian political education currently shows a significant gap between the growing number of political parties and the quality of political education produced. Scholars such as Omar Muhammad al-Toumy al-Syaibany, Hassan Langgulung, and Muhammad Quthb assert that educational success is fundamentally determined by the quality of methods used, not merely the content of the curriculum. Using qualitative interpretive methodology with a thematic Qur'anic approach (mawdhu'i), this study identifies at least 32 political education methods practiced by the Prophet, producing three primary domains of transformative change: 11 Cognitive methods, 19 Affective methods, and 2 Psychomotor methods. These methods are rooted in the Qur'anic principles of Surah al-Nahl verse 125 hikmah, mau'izhah hasanah, and mujadalah. Implementation within the family unit is identified as the key to societal transformation, as the family constitutes the first and most decisive institution for cultivating political consciousness in successive generations